Investigation of assessment on the implementation of rules and regulations related to tender and quotation of works for UiTM projects / Prof. Ir. Dr. Zainab Mohamed … [et al.] - Mohamed, Prof. Ir. Dr. Zainab (Research Management Institute (RMI), 2011)
Contractor selection is one of the most important aspects in the completion of UiTM construction projects. The successfulness of a construction project depends on the "right" contractor being selected. During the 'Lembaga Perolehan' 33rd meeting on the 4th August 2009, the Assistant Vice Chancellor requested for a study to be conducted with the main objective is to evaluate and assess the existing rules and regulation related to tender and quotation procedure in UiTM tender process for works and services projects. The main scope of this research is to identify and assess the existing procedure that has been implemented in UiTM and comparing it with the procedure of other agencies in Malaysia and to propose recommendations to UiTM for improvement of the tender process and evaluation. The data gathered for this project were mainly from the Pejabat Pembangunan, Pejabat Pengurusan Fasiliti of UiTM and from interview sessions with personnel from other agencies. The agencies involved were Tenaga Nasional Berhad (TNB), Telekom Malaysia (TM), Public Work Department (PWD) and Department of Irrigation and Drainage (DID). The interviews conducted were to evaluate processes, as well as looking into the standard guidelines used by them. The first objective is to investigate the actual implementation of existing assessment of the tender and quotation of works and services for UiTM projects. Findings indicate that there were two (2) methods being used, which are the cut-off method and department estimation. The cut-off method provides a certain degree of transparency to the tender evaluation process as the optimum tender price will be governed only by the tenders received and not by other parties involved in the tender process. However, whether the Pejabat Pembangunan and Pejabat Pengurusan Fasiliti of UiTM did actually follow the procedures were not certain at this stage. There is a need for further investigation using research tools such as an observation of an actual tender evaluation process and a detailed documentation research.